Combating Klebsiella pneumoniae: from antimicrobial resistance mechanisms to phage-based combination therapies - Ding, Jiaxin; Yan, Weilei; Zheng, Rui; Ma, Mengye; Jiang, Liming (Frontiers in Cellular and Infection Microbiology, 2025)
Klebsiella pneumoniae (K. pneumoniae) is a central pathogen in both nosocomial and community-acquired infections worldwide, capable of causing pneumonia, urinary tract infections (UTIs) and bacteremia. In recent years, the spread of multi-drug resistant (MDR) bacterial pathogens has become a major public health challenge. Traditional antibiotics, which are increasingly ineffective due to escalating resistance, significant adverse effects, and limited therapeutic efficacy, underscore the urgent need for novel strategies. The primary antimicrobial resistance mechanisms of K. pneumoniae currently include alterations of drug target sites, modified enzyme-mediated antibiotic inactivation, permeability barriers to antimicrobial agents, active efflux systems, synergistic resistance mechanisms involving biofilm-persisters-quorum sensing (QS) and heteroresistance. While phage therapy offers precise targeting of pathogenic bacteria, its standalone use is hampered by obstacles such as the rapid evolution of bacterial resistance and narrow host ranges. Accordingly, combinatorial phage therapy has emerged as a key research focus. In this review, we not only summarize the multidimensional antimicrobial resistance mechanisms of K. pneumoniae and the principles of synergistic phage strategies but also evaluate the potential for clinical translation and current challenges, providing a theoretical framework for the precise treatment of multidrug-resistant K. pneumoniae (MDRKP) infections, so as to promote the clinical application of phage-based combination therapy in the post-antibiotic era. Beyond summarizing recent advances, this work also provides a unique translational perspective by critically evaluating the synergy, clinical applicability, and challenges of combinatorial phage approaches—including phage-antibiotic, phage-AMP, and phage-nanocarrier therapies—against MDRKP, filling a critical gap in existing reviews.